The Impact of Doomscrolling on the Mental Health of Social Media Users: A Systematic Literature Review - Hanifa Ashaditya Khamila Putri; Siti Maimunah (Al-Qalam Institue, 2026)
The rapid growth of social media has significantly increased access to information while simultaneously intensifying exposure to negative content, thereby contributing to the emergence of doomscrolling behavior. This phenomenon has attracted increasing attention in media psychology due to its potential role in deteriorating users’ mental health. The present study aims to analyze the influence of doomscrolling on mental health and to identify the psychological mechanisms underlying this relationship among adult social media users. The study employed a Systematic Literature Review (SLR) approach following the PRISMA guidelines. Literature searches were conducted in the Scopus database using Publish or Perish, while article screening and duplicate removal were performed using Rayyan. Of the 59 records initially identified, 14 international studies published between 2022 and 2025 met the inclusion criteria and were analyzed through thematic synthesis. The findings indicate that doomscrolling is a maladaptive digital behavior shaped by the interaction of the need for certainty, threat-related attentional bias, and social media algorithmic reinforcement. Doomscrolling was consistently associated with increased anxiety, depression, psychological distress, sleep disturbances, post-traumatic stress disorder (PTSD), reduced mental well-being, and existential anxiety. This study proposes a conceptual model explaining the psychological pathway linking doomscrolling to declining mental health and contributes to the advancement of digital media psychology literature. The findings have practical implications for the development of digital literacy programs, emotional regulation skills, and preventive mental health interventions in the digital era.